2004
DOI: 10.1534/genetics.104.028027
|View full text |Cite
|
Sign up to set email alerts
|

Lrg1p Is a Rho1 GTPase-Activating Protein Required for Efficient Cell Fusion in Yeast

Abstract: To identify additional cell fusion genes in Saccharomyces cerevisiae, we performed a high-copy suppressor screen of fus2⌬. Higher dosage of three genes, BEM1, LRG1, and FUS1, partially suppressed the fus2⌬ cell fusion defect. BEM1 and FUS1 were high-copy suppressors of many cell-fusion-defective mutations, whereas LRG1 suppressed only fus2⌬ and rvs161⌬. Lrg1p contains a Rho-GAP homologous region. Complete deletion of LRG1, as well as deletion of the Rho-GAP coding region, caused decreased rates of cell fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 77 publications
3
31
0
2
Order By: Relevance
“…Additionally, lrg1/lrg1 diploids do not cluster (Figure 1), and the wall and septum thicknesses of these cells were not statistically different from those of wild-type haploids ( Figure 5). Our results, in conjunction with the recent report that LRG1 localizes to the tip of the mating projection in haploids and is required for efficient cell fusion (Fitch et al, 2004), suggest that matingspecific glucan synthase machinery and regulatory proteins are downregulated in cells that have undergone cell fusion. Since we observed clustering in pseudodiploid lrg1 cells, deactivation of the mating pathway alone is not sufficient to suppress the clustered phenotype.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Additionally, lrg1/lrg1 diploids do not cluster (Figure 1), and the wall and septum thicknesses of these cells were not statistically different from those of wild-type haploids ( Figure 5). Our results, in conjunction with the recent report that LRG1 localizes to the tip of the mating projection in haploids and is required for efficient cell fusion (Fitch et al, 2004), suggest that matingspecific glucan synthase machinery and regulatory proteins are downregulated in cells that have undergone cell fusion. Since we observed clustering in pseudodiploid lrg1 cells, deactivation of the mating pathway alone is not sufficient to suppress the clustered phenotype.…”
Section: Discussionsupporting
confidence: 82%
“…Further analysis revealed that Ste12, which regulates expression of genes downstream of the mating and filamentous growth MAPK pathway but is also known to function in the cell integrity pathway (see review by Elion, 2000), was required for cell clustering. LRG1 has previously been identified as a regulator of glucan synthesis (Lorberg et al, 2001;Roumanie et al, 2001;Watanabe et al, 2001;Fitch et al, 2004), and our results suggest that the observed 'clustered' phenotype is a consequence of failed mother-daughter separation due to increased glucan production at the bud site.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…In a similar way, given the known interactions between Mpt5p and elements of the m-MAPK pathway, it is possible that deletion of MPT5 leads to a low-level activation of this pathway. Lrg1p could also constitute an element of this system: the protein is required for efficient cell fusion (Fitch et al 2004) and its expression is inhibited by Mpt5p; thus deletion of MPT5 would lead to increased levels of Lrg1p and improved cell fusion.…”
Section: Discussionmentioning
confidence: 99%